Rekonstruksi buku ajar berbasis kurikulum merdeka: Pengembangan E-Book Bahasa Inggris Berbasis Nilai Budaya untuk Fase E - Nur, Luluk Choirun Nisak (EDUSCOPE: Jurnal Pendidikan, Pembelajaran, dan Teknologi, 2024)
This research aims to develop a Culture-based English e-book aligned with the Merdeka Curriculum for Phase E in MA Al-Bairuny, Jombang. The Merdeka Curriculum is expected to provide a more contextual and culturally relevant learning experience for students. Using the ADDIE method (Analysis, Design, Development, Implementation, Evaluation), this study focuses on the validation of the e-book product.The analysis phase identified the needs of students and teachers, highlighting that the current curriculum does not adequately address the cultural diversity of the students. The design phase resulted in an e-book with English content focusing on text types rooted in Indonesian culture. Material and media validation were conducted by education and media experts, resulting in "excellent" ratings for both aspects. Implementation involved student response testing, which showed high satisfaction with the e-book.The findings of this research confirm that the e-book aligns with the Merdeka Curriculum, integrates cultural values, and receives positive feedback from students. This e-book can serve as a relevant alternative to enhance English language learning in Phase E and should be expanded for broader use.